Enabling Technologies in the Problem Solving Environment HEDP (Communications in Computational Physics, 2008)
Enabling technologies are those technologies preparing input data, analyzing output data and facilitating the whole processes for numerical simulations. Thispaper outlines current enabling technologies for large-scale multidisciplinary simulations used in the High End Digital Prototyping (HEDP) system, a problem solving environment equipped with capability of mesh generation and large-scale visualization.A problem solving environment is a computer system that provides all the computational facilities necessary to solve a target class of problems. Mesh generation continues to be the pacing technology for a practical numerical analysis, which is essentialto yielding an accurate and efficient solution. Large-scale visualization maps the massive data to some kinds of scenes interactively, which can be realized through a tileddisplay wall system with distributed visualization capability. HEDP is designed forlarge-scale and multidisciplinary simulations, and there are four categories of modulesinvolved, namely pre-processing module, computing module, post-processing module, and platform control module. All these modules are coupled through a softwarebus, which makes the modules integrated seamlessly. Detailed design principles andapplications of the HEDP environment are addressed in this paper.